Exploring variation in clinicians’ perception and approach towards adults with ADHD - Sarrami Foroushani, Pooria (2009)
There are various views towards Attention Deficit Hyperactivity Disorder (ADHD) and the recent introduction of the disorder for adults has added to the controversies. I intend to explore variation in clinicians’ perception and approach towards adults with ADHD. I produced a vignette describing an adult with a diagnosis of ADHD and sent it to 150 clinicians. I received 44 replies, and performed 16 semi-structured interviews. I found participants suggested various diagnoses, causes of the problem, treatments, and the appropriate professional group for the vignette. Participants confirmed the existence of variation in the clinicians’ perception and approach. Their views also suggested that the different characteristics of clinicians, diagnostic methods, psychiatric disorders, the possibility of access to different information and social factors were contributing to the variation. In addition, my analysis indicated that participants might have different perceptions according to their experience, awareness and work-settings. I found that the variation might be also related to the inclination of participants towards particular disorders or styles of practice, and hermeneutical factors. Finally, I produced a model that illustrates a relationship between different factors with the variations in clinicians’ perception and approach. In conclusion, I suggested the dependency of diagnosis on clinicians, the possibility of a variation in their knowledge, and gaps between research and practice. I described different types of competition that exist in the process of the medicalization of ADHD. Finally, I discussed directions for future investigations.